First DNA metabarcoding diet assessment on the critically endangered Tricolour Langur, Presbytis chrysomelas cruciger - Roberta Chaya Tawie, Tingga; Jack, Liam; Bilhan, Deli; Mohd Luqman, Anuar; Ahmad, Ampeng; Badrul Munir, Md Zain (Pensoft Publishers, 2024)
Presbytis chrysomelas cruciger or also known as the Tricolour langur—is rare, endemic to Sarawak and Kalimantan in Borneo and classified as a critically endangered subspecies. The current P. c. cruciger population size is uncertain because the numbers are continuously decreasing. At present, there is no comprehensive scientific report on P. c. cruciger in Sarawak, although this subspecies is known to inhabit Maludam area. Recent first sighting of P. c. cruciger in Jemoreng Sarawak presents a research opportunity to study its feeding from a molecular ecology perspective. Herein, we report the first findings on the dietary intake of P. c. cruciger using a high-throughput DNA metabarcoding approach. We emphasise the diet intake of P. c. cruciger from Jemoreng Protected Forest in Sarawak using DNA metabarcoding of the trnL region. Preliminary findings revealed 11 amplicon sequence variants (ASV) classified into one phylum, four classes, four orders, four families, three genera and three plant species. Fibraurea tinctoria (akar kuning; Family Menispermaceae), Poikilospermum suaveolens (akar jangkang; Family Urticaceae) and Litchi chinensis (lychee; Family Sapindaceae) were the three main plant species that were consumed by P. c. cruciger. Understanding the dietary intake of P. c. cruciger is of paramount importance for their conservation and management of the habitat areas where their population resides.